Peduli Mahasiswa Terhadap Sanitasi Lingkungan Pasar Tradisional Motamasin-Betun - Yohana Febriana Tabun; Stefania Sonia Manek; Ivony Sarlin Asa; Damian Puling; Yanuarius Bria Seran; Wolfgang Asindo Seran (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
In an effort to improve the quality of environmental sanitation in traditional markets, this community service program involves students as agents of change. Traditional markets are often a gathering place for various wastes and impurities, which can have a negative impact on public health. This activity aims to increase public awareness and knowledge, especially traders and market visitors, about the importance of environmental sanitation. Through the social services carried out, students provide information about good sanitation practices and how to maintain a clean environment. The results of this activity are expected to create positive changes, improve public health, and make traditional markets a clean and comfortable place. This program is not only beneficial to the community, but also a valuable experience for students in applying the knowledge they learn, as well as developing social concern and responsibility for the environment.